Computationally Driven Discovery of Layered Quinary Oxychalcogenides: Potential p-Type Transparent Conductors? - Watson, Graeme (My University, 2020)
n-type transparent conductors (TCs) are key materials in the modern optoelectronics industry. Despite years of research, the development of a high-performance p-type TC has lagged far behind that of its n-type counterparts, delaying the advent of “transparent electronics”-based p-n junctions. Here, we propose the layered oxysulfide [Cu2S2][Sr3Sc2O5] as a structural motif for discovering p-type TCs. We have used density functional theory to screen 24 compositions based on this motif in terms of their thermodynamic and dynamic stability and their electronic structure, thus predicting two p-type TCs and eight other stable systems with semiconductor properties. Following our predictions, we have successfully synthesized our best candidate p-type TC, [Cu2S2][Ba3Sc2O5], which displays structural and optical properties that validate our computational models. It is expected that the design principles emanating from this analysis will move the field closer to the realization of a high figure-of-merit p-type TC.
PUBLISHED
Keywords: Mixed anion semiconductors; Transparetn conductors; P-type; Inorganic; Photocatalysts; Photovoltaics; DFT; Materials prediction; Oxychalcogenides; Layered compounds